Photodynamic effect of zinc porphyrin on the promastigote and amastigote forms of Leishmania braziliensis. Issue 4 (27th March 2018) - Andrade, C. G.; Figueiredo, R. C. B. Q.; Ribeiro, K. R. C.; Souza, L. I. O.; Sarmento-Neto, J. F.; Rebouças, J. S.; Santos, B. S.; Ribeiro, M. S.; Carvalho, L. B.; Fontes, A.
Abstract : Zn(ii ) meso -tetrakis( N -ethylpyridinium-2-yl)porphyrin was applied in the photodynamic inactivation of Leishmania braziliensis, leading to considerable cell damage. Abstract : Leishmaniasis is a neglected disease present in more than 88 countries. The currently adopted chemotherapy faces challenges related to side effects and the development of resistance. Photodynamic therapy (PDT) is emerging as a therapeutic modality for cutaneous leishmaniasis. Zn(ii ) meso -tetrakis( N -ethylpyridinium-2-yl)porphyrin (ZnTE-2-PyP 4+, ZnP) is a cationic, water-soluble, zinc porphyrin-based photosensitizer whose photodynamic effect on Leishmania braziliensis was analyzed by evaluating the number of visibly undamaged and motile cells, cell membrane integrity, mitochondrial membrane potential, and ultrastructural damage. Treatment of parasites with ZnP and light induced damage in up to 90% of L. braziliensis promastigote cells. Propidium iodide labeling suggested the loss of plasma membrane integrity. In samples treated with ZnP and light, a hyperpolarization of the mitochondrial membrane potential was also observed. Ultrastructural evaluation of promastigotes after photodynamic treatment indicated a loss of cytoplasmic material and the presence of vacuoles. Scanning electron microscopy showed wrinkling of the plasma membrane and a reduced cell volume. Additionally, the number of amastigotes per macrophage was reduced by about 40% after photodynamic application. The treatment showed no considerable toxicity against mammalian cells. Therefore, the results indicated that PDT associated with ZnTE-2-PyP 4+ represents a promising alternative to cutaneous leishmaniasis treatment.